Prevalence and factors associated with health insurance coverage in urban sub-Saharan Africa: Multilevel analyses of demographic and health survey data. - Hubert Amu; Kwamena Sekyi Dickson; Kenneth Setorwu Adde; Kwaku Kissah-Korsah; Eugene Kofuor Maafo Darteh; Akwasi Kumi-Kyereme (PLoS ONE, 2022)
Introduction With the vision of achieving Universal Health Coverage (UHC) by the year 2030, many sub-Saharan African (SSA) countries have implemented health insurance schemes that seek to improve access to healthcare for their populace. In this study, we examined the prevalence and factors associated with health insurance coverage in urban sub-Saharan Africa (SSA). Materials and methods We used the most recent Demographic and Health Survey (DHS) data from 23 countries in SSA. We included 120,037 women and 54,254 men residing in urban centres in our analyses which were carried out using both bivariable and multivariable analyses. Results We found that the overall prevalence of health insurance coverage was 10.6% among females and 14% among males. The probability of being covered by health insurance increased by level of education. Men and women with higher education, for instance, had 7.61 times (95%CI = 6.50-8.90) and 7.44 times (95%CI = 6.77-8.17) higher odds of being covered by health insurance than those with no formal education. Males and females who read newspaper or magazine (Males: AOR = 1.47, 95%CI = 1.37-1.57; Females: AOR = 2.19, 95%CI = 1.31-3.66) listened to radio (Males: AOR = 1.29, 95%CI = 1.18-1.41; Females: AOR = 1.42, 95%CI = 1.35-1.51), and who watched television (Males: AOR = 1.80, 95%CI = 1.64-1.97; Females: AOR = 1.86, 95%CI = 1.75-1.99) at least once a week had higher odds of being covered by health insurance. Conclusion The coverage of health insurance in SSA is generally low among urban dwellers. This has negative implications for the achievement of universal health coverage by the year 2030. We recommend increased public education on the benefits of being covered by health insurance using the mass media which we found to be an important factor associated with health insurance coverage. The focus of such mass media education could target the less educated urban dwellers, males in the lowest wealth quintile, and young adults (15-29 years).